Aswaja Challenge In Globalization Era - Abdul Muid (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2017)
Abstraction: Thinking aswaja is thinking that human life should not only rely on reason but be able to understand and live that the aqli argument should be placed under the Naqli proposition